History of Social Responsibility: The Indonesian Government Role in Economy Development - Sinaga, Rifeald Romauli; Bowden, Bradley (Journal of Applied Business and Economics, 2018)
The paper explores the history of Social Responsibility (SR) in Indonesia, highlighting the role of the Indonesian government as both a driver of SR as well as key player. The central role of the state in Indonesian SR, it is argued, reflects government enterprises were central to the economy, and the immediate post-independence period, when SOEs were used as a means of displacing Dutch interests. Continued government influence is found in Indonesian regulations that since 2007 have explicitly. An understanding of the Indonesian government’s SR role helps fill the comparative void in the SR historical literature dealing with the Third World.